Q. 173.8( 8 Votes )

If the sum of the

Answer :

equation is x2 – x = λ (2x – 1)

x2 – x – λ (2x – 1) = 0


x2 – (2λ + 1)x + λ = 0


Here a = 1, b = – (2λ + 1), c = λ


Sum of the roots = – b/a


–(– (2λ + 1)) = 0


λ = – 1/2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses